1995
DOI: 10.1007/bf02251257
|View full text |Cite
|
Sign up to set email alerts
|

Missed opportunities: Psychological ramifications of counterfactual thought in midlife women

Abstract: Counterfactual thinking entails the process of imagining alternatives to reality--what might have been. The present study examines the frequency, content, and emotional and cognitive concomitants of counterfactual thinking about past missed opportunities in midlife women. At age 43, nearly two-thirds of the sample of educated adult women reported having missed certain opportunities at some time in their lives. Most of the counterfactual thoughts concerned missed opportunities for greater challenge in work. Emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 41 publications
4
55
0
Order By: Relevance
“…Negative emotions signal that a problem needs rectifying. Often it is too late to do anything about something bad that has already happened, but counterfactual thinking can enable the person to learn a lesson so as to avoid repeating the misfortune in the future (Landman, Vandewater, Stewart, & Malley, 1995;Markman, Gavanski, Sherman, & McMullen, 1993;Roese, 1994;Taylor & Schneider, 1989).…”
Section: Emotion and Learning In Daily Lifementioning
confidence: 99%
“…Negative emotions signal that a problem needs rectifying. Often it is too late to do anything about something bad that has already happened, but counterfactual thinking can enable the person to learn a lesson so as to avoid repeating the misfortune in the future (Landman, Vandewater, Stewart, & Malley, 1995;Markman, Gavanski, Sherman, & McMullen, 1993;Roese, 1994;Taylor & Schneider, 1989).…”
Section: Emotion and Learning In Daily Lifementioning
confidence: 99%
“…Finally, three studies are briefly summarized that rule out an alternative interpretation of the opportunity principle centering on framing effects. Overall, five data sets used the method of having participants select their biggest regrets from a list provided by the researchers (DeGenova, 1992; Landman & Manis, 1992, Samples 1 and 2;Landman et al, 1995); the remainder used the strategy of having participants record regrets, with independent coders subsequently assigning them to life domain categories. Also, in three of the data sets (Landman et al, 1995;Lecci et al, 1994;Wrosch & Heckhausen, 2002), the researchers restricted their measure to regrets of 1 One commonly cited paper did not appear in the meta-analysis (Metha, Kinnier, & McWhirter, 1989) because it seemed that its data were redundant to those presented in Kinnier and Metha (1989).…”
Section: Current Researchmentioning
confidence: 99%
“…The Hattiangadi et al (1995) data for example show that inactions outnumbered actions by more than four to one, and that does not include a category of "indeterminate regrets" (those coded as "both" or "neither") which in the studies reported in the thesis were on average three times more likely to be general than specific. It would not be surprising to find similar patterns in surveys asking people to say what they would do if they had their lives to live over (DeGenoa, 1992;Hattiangadi et al, 1995;Kinnier & Metha, 1989;Landman & Manis, 1992;Landman et al, 1995) because as Kahneman (1995) has suggested, requests for regrets tend to elicit elaborative counterfactuals about how life might have been better, which are likely to involve big changes of a general nature. In temporal construal terms (Trope & Liberman, 2003) such requests might be interpreted as an invitation to consider personal goals at the superordinate level, which would necessarily elicit "bigger picture" construals of distant events.…”
Section: Factors That Make General Inactionsmentioning
confidence: 84%
“…These findings come from surveys and experimental studies involving both sexes, all age groups, and different methods of eliciting regret. Some studies asked people directly what they regretted in life (Gilovich & Medvec, 1994;Jokisaari, 2003) or which of life"s activities they most regretted not having pursued (Wrosch & Heckhausen, 2002), while others asked people to say how they would do things differently if they could live life over again (DeGenoa, 1992;Hattiangadi, Medvec & Gilovich, 1995;Kinnier & Metha, 1989;Landman & Manis, 1992;Landman, Vanderwater, Stewart & Malley, 1995). Lecci, Okun and Karoly, (1994) asked people about their unfulfilled goals, which were seen as proxies for regret.…”
Section: Who Experiences Regret What Do People Regret and Why?mentioning
confidence: 99%
See 1 more Smart Citation